Original articleCorrelation of neuroradiological, electroencephalographic and clinical findings in cortical dysplasias in children - Mazurkiewicz-Bełdzińska, Maria; Szmuda, Marta; Matheisel, Agnieszka (Folia Neuropathologica, 2006)
Introduction: Cortical dysplasias (CD) are defined as malformations of cortical development. They result from impairment of neuronal proliferation, migration and differentiation. CD are common pathological substrates in patients with early-onset childhood epilepsy and/or developmental delay as well as neurological signs. Recognition of the importance of cortical dysplasias has been shown in many studies when introducing structural MRI. The following study was performed in order to correlate the neuroimaging findings with the electroencephalographic and clinical picture of children with cortical dysplasias. Materials and methods: 46 patients with the presence of CD features in MRI were identified. There were 18 female and 28 male patients. The age ranged from 3 months to 12 years (mean age = 6.2, median age = 3.1). The objectives of the study were explained to the parents or legal representatives of children when possible and also informed consent was obtained. Multiple EEG recordings as well as detailed clinical analysis of all patients were performed. Statistical analysis was conducted in order to correlate the type of CD with clinical outcome and electrophysiological findings. Results: There were 31 patients with focal dysplasias, 6 with schizencephaly, 4 with heterotopias, 3 lissencephaly and 2 with band heterotopia. 80% presented epilepsy (60% of them drug-resistant). Additionally, we tried to elucidate the clinical characteristics of epilepsy. In 75% of epilepsy patients the electroencephalographic changes correlated with anatomical localization of CD. 74% of patients were mentally retarded and 30% had focal neurological deficits. Conclusions: There were no correlations between the type of CD and the severity of the clinical picture, especially the level of mental retardation and presence of drug-resistant epilepsy. Different age at epilepsy onset and various responsiveness to antiepileptic drugs in the majority of patients may reflect different dynamics in epileptogenicity of the underlying CD.